Age and Defect Size as Predictors of Pulmonary Hypertension in Secundum Atrial Septal Defect: A Retrospective Study from the Himalayan Region - Koirala, Ishita; Panthee, Nirmal; Adhikari, Anu; Timilsina, Pratikshya; Thapa, Awesh; Acharya, Sampada; Pradhan, Sidhartha; Koirala, Raamesh (Nepalese Heart Journal, 2025)
Background and aims: Atrial septal defect is a common congenital heart disease. Most patients are asymptomatic. The incidence and progression of pulmonary hypertension in these defects have important clinical implications. We sought to establish the role of age and defect size as predictors of pulmonary hypertension. Methods: Hospital discharge summaries of patients who underwent surgical defect closure by a single unit of Shahid Gangalal National Heart Center between 2018 and 2023 were retrospectively reviewed. Baseline variables and echocardiography data were analyzed using SPSS. Pulmonary artery systolic pressure of > 50 mmHg in echocardiography was used to define pulmonary hypertension. A p-value of <.05 was considered significant. Results: A total of 407 patients underwent atrial septal defect closure during that period, with a mean age being 22.1±12.5 (3-55) years and one-third (32.2%) being males. The majority (84.6%) were in NYHA I or II functional class. Mean pulmonary artery systolic pressure was 47.0±11.8 (24-113)mmHg. Mean indexed defect size was 2.2±0.8 (1.1-6.0) cm/m2. Age had a positive correlation of 0.38 with pulmonary artery systolic pressure (p <.001). Interestingly, indexed defect size had a negative correlation of .15 with pulmonary artery systolic pressure (p=.002). Multiple regression showed only age as the significant factor predicting pulmonary hypertension with a standardized beta of .357 (p<.001). Receiver operating characteristic curve analysis showed an area under the curve of. 733, p<.001 for age and pulmonary artery systolic pressure. Conclusions: Patients’ age and not the indexed size of the defect dictate the development of pulmonary artery hypertension in patients with secundum atrial septal defects.